Effect of Exercise on Quality of Sleep in COVID-19 Patients: A Meta-Analysis - Septyandi Ramadhan; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, 2023)
Background: Coronavirus occurs because the virus lowers the body immune, which can lead to several things such as decreased sleep quality. Gymnastics is one exercise that can improve sleep quality, gymnastics can also reduce stress levels and anxiety. This study aims to discover the effect of gymnastics on sleep quality in COVID-19 patients. Subjects and Method: It was a systematic review and meta-analysis of primary studies. Article searches were conducted based on PICO model eligibility criteria. Population: COVID-19 patients. Intervention: administration of gymnastic intervention. Comparison: no gymnastics intervention. Outcome: improved sleep quality. Article search was conducted through journal databases including Google Scholar, MEDLINE/PubMed, Science Direct, Hindawi, BMC, Europe PMC, and Springer Link using search keywords: